PERSEPSI REMAJA TERHADAP KONTROL PERILAKU HIV/AIDS - Athiutama, Ari; Febriani, Indra; Dewi, Rusmala; Arma, A Muhtadi; Ananda, Wahyuni (Prodi Keperawatan Tegal Program Diploma III Poltekkes Kemenkes Semarang, 2025)
HIV/AIDS causes many impacts on adolescents, which ultimately affect their families and communities. This happens due to ignorance and misinformation, resulting in poor perception and behavioral control among adolescents. The purpose of this study was to determine the relationship between adolescents' perceptions and their HIV/AIDS behavioral control. This study used quantitative methods with a cross sectional design. The sampling technique was accidental sampling, with 86 respondents. Data were collected using a questionnaire and then analyzed univariately and bivariately using the Chi-square test. The results of the study showed that the majority of adolescents' perceptions were in the good category (76.7%), the majority of behavioral control was in the good category (72.1%) and there was a significant relationship between adolescents' perceptions and HIV/AIDS behavioral control (p value = 0.001). Adolescents' perceptions are linked to their HIV/AIDS behavioral control. Positive perceptions will improve their HIV/AIDS behavioral control. Adolescents' perceptions can influence their behavioral control, so maximizing positive perceptions is crucial for behavioral control.